DETERMINASI AUDIT INTERNAL DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE SERTA IMPLIKASINYA PADA KINERJA BANK - Dedi Kusmayadi (University of Merdeka Malang, 2012)
The objective of the research was to find out the effect of internal audit on good corporate governance and itsimpact to performance of government bank Tasikmalaya regency. The method used in the research was censusmethod with descriptive explanatory approach. The data collecting technique used to obtain the primary datawas through interviews and by means of questionnaire. Path analysis was used to analyze the data.The resultsshowed that: the internal audit gave positive and significant effect on good corporate governance, the internalaudit and good corporate governance, partially and simultaneously gave positive and significant effect onperformance of government bank Tasikmalaya regency.